2021
DOI: 10.1063/5.0035601
|View full text |Cite
|
Sign up to set email alerts
|

Bone tissue engineering via application of a collagen/hydroxyapatite 4D-printed biomimetic scaffold for spinal fusion

Abstract: The fabrication of biomimetic scaffolding is a challenging issue in tissue engineering. Scaffolds must be designed with micrometer precision to enable cell proliferation and tissue growth, requiring customization based on the type of tissue being developed. Biomimetic scaffolds have attracted interest for their potential in spinal fusion applications. By providing a structured environment to promote osteogenesis, these materials offer a robust and minimally invasive means to fuse vertebrae. The present study d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…As such, G/H scaffolds fabricated in this study have a much lower modulus compared to natural bones. Similarly, previous reports have suggested that the main limitation of collagen or gelatin based hydroxyapatite is the low mechanical strength 8 . Lin et al, have reported that the 3D printed collagen/hydroxyapatite has the range of 0.09 ~ 0.15 MPa in the elastic modulus 39 , and Zhang et al, also reported that bulk gelatin/hydroxyapatite scaffolds have 0.2 MPa of maximum strength 60 .…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…As such, G/H scaffolds fabricated in this study have a much lower modulus compared to natural bones. Similarly, previous reports have suggested that the main limitation of collagen or gelatin based hydroxyapatite is the low mechanical strength 8 . Lin et al, have reported that the 3D printed collagen/hydroxyapatite has the range of 0.09 ~ 0.15 MPa in the elastic modulus 39 , and Zhang et al, also reported that bulk gelatin/hydroxyapatite scaffolds have 0.2 MPa of maximum strength 60 .…”
Section: Resultsmentioning
confidence: 70%
“…Using the 3D printing method, the 3D specific architecture of the artificial bone matrix can be easily achieved. The controllability of pore geometries and internal pore structures can also provide sufficient spatial space for forming new blood vessels that are required to regenerate volumetric bone tissue and metabolic activities between the construct and the environment 8 . The highly personalizable strengths of the 3D printing can be adapted to bone defects with various types of structures, such as fully interconnected pore structure 9 , hierarchical structure 10 , fibrous structure 11 , and cell- or growth factors- laden structure 12 for bone tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…These scaffolds showcased a 95.77% shape memory effect in the presence of a thermal stimulus, and its in vitro cytocompatibility and hydrophilic nature make it a potential candidate for customized biomedical applications. In a recent study, 116 a hierarchical biomimetic collagen/hydroxyapatite scaffold was prepared. The microchannels present in each strut of the biomimetic scaffold demonstrate significant in vitro osteogenic activity and increased bone formation and blood vessel ingrowth in vivo for spinal fusion in a mouse.…”
Section: D Resorbable Hap-based Scaffoldsmentioning
confidence: 99%
“…Microchannel-guided formation of aligned units has been utilized in a broad range of target tissues, including bone, nervous tissues, and vasculatures ( Daly et al, 2018 ; Huang et al, 2018 ; Lee et al, 2020 ; Hwangbo et al, 2021 ). Sacrificial hydrogels—deposited as a temporary structure for structural support or generation of certain structures—are often removed by variations in temperature once the crosslinking of the engineered construct is complete; therefore, they have been widely adopted in 3D bioprinting for establishing built-in channels.…”
Section: D Biofabrication Technologies In Skeletal Muscle Engineeringmentioning
confidence: 99%